IBM PENDAMPINGAN HKI ATAS MEREK UNTUK PERLINDUNGAN HUKUM PRODUK BARANG DAN JASA UMKM DI KABUPATEN SITUBONDO - Muhammad Yusuf Ibrahim; Sudiyono Sudiyono (Relawan Jurnal Indonesia, 2017)
Brand represents the identification mark of a product of goods and services. Brands can also provide information to consumers about a product of goods and services produced by the manufacturers. Even the brand can show the quality of a product of goods and services. To obtain a legal protection of brands, the owner of the brands shall register its brands as set forth in article 3 of Act Number 15 of 2001 on brands, that is, the right to trademark is an exclusive right granted by the state to the owner of the brands registered in the General Register of brands for a certain period of time by using its own brand or giving permission to other parties to use it. Currently, Micro, Small, and Medium (MSME) in Situbondo District has grown very rapidly. As a business wheel in the region, many UMKM start a business by focusing on the development of products and services without regard to the legal protection of the brands that have been made; thus, many brands made by business actors in areas are still not registered at the Directorate General of Intellectual Property Rights. The lack of information and knowledge of Intellectual Property Rights (IPR) in the regions increasingly makes the business actors in the regions do not pay attention to the Intellectual property owned. Therefore, if in the future there are products of the same goods and services as those made by other business actors with registered trademarks, then business actors will be harmed. To avoid this, then research on intellectual property rights is made.